Estudio económico social sobre la implementación de un parque industrial en la parroquia San Camilo sector sur de cantón Quevedo. Periodo 2012 - Muñoz Jordan, Irvin Lenin (2015)
This research was based on an economic study - social to find the feasibility of implementing an industrial park in the parish San Camilo Quevedo Canton southern sector. By conducting market research via surveys, 96% of people said they believe favor the installation of the industrial park and in turn 59% of owners said that MSMEs would be willing to part with their businesses the new industrial park With the feasibility study tried to find the best location of the industrial park as a result leaving St. Camillus Parish - Eco route as an area of large tracts of land without producing. Also the company will feature 23 people which exercise positions CEO, accountant, 2 secretaries, 1 Legal Adviser, 1 Administrative Head, 8 maintenance and cleaning and 8 guards……………..